Hierarchical domain‐motion analysis of conformational changes in sarcoplasmic reticulum Ca2+‐ATPase. Issue 4 (10th February 2015) - Kobayashi, Chigusa; Koike, Ryotaro; Ota, Motonori; Sugita, Yuji
ABSTRACT: Sarco(endo)plasmic reticulum Ca 2+ ‐ATPase transports two Ca 2+ per ATP‐hydrolyzed across biological membranes against a large concentration gradient by undergoing large conformational changes. Structural studies with X‐ray crystallography revealed functional roles of coupled motions between the cytoplasmic domains and the transmembrane helices in individual reaction steps. Here, we employed "Motion Tree (MT), " a tree diagram that describes a conformational change between two structures, and applied it to representative Ca 2+ ‐ATPase structures. MT provides information of coupled rigid‐body motions of the ATPase in individual reaction steps. Fourteen rigid structural units, "common rigid domains (CRDs)" are identified from seven MTs throughout the whole enzymatic reaction cycle. CRDs likely act as not only the structural units, but also the functional units. Some of the functional importance has been newly revealed by the analysis. Stability of each CRD is examined on the morphing trajectories that cover seven conformational transitions. We confirmed that the large conformational changes are realized by the motions only in the flexible regions that connect CRDs. The Ca 2+ ‐ATPase efficiently utilizes its intrinsic flexibility and rigidity to response different switches like ligand binding/dissociation or ATP hydrolysis. The analysis detects functional motions without extensive biological knowledge of experts, suggesting its general applicability to domain movements in other membrane proteins to deepen the understanding of protein structure and function. Proteins 2015; 83:746–756. © 2015 Wiley Periodicals, Inc.